a. ( 5x – 4) mũ 2 – 49x mũ 2 b. 9(2x + 3) mũ 2 – 4(x+1) mũ 2 c.(3x +1) mũ 2 – 4(x-2) mũ 2 d. 16(4x+5) mũ 2 – 25(2x + 2 ) mũ 2 e. 4x mũ 2 (x-y) + 9y m

Question

a. ( 5x – 4) mũ 2 – 49x mũ 2
b. 9(2x + 3) mũ 2 – 4(x+1) mũ 2
c.(3x +1) mũ 2 – 4(x-2) mũ 2
d. 16(4x+5) mũ 2 – 25(2x + 2 ) mũ 2
e. 4x mũ 2 (x-y) + 9y mũ 2 ( y-x)
f. 4x mũ 3 + 24x mũ 2 – 12xy mũ 2
mình cần gấp ạ
cảm ơn mọi người

in progress 0
Claire 3 tuần 2021-07-08T17:24:21+00:00 1 Answers 1 views 0

Answers ( )

    0
    2021-07-08T17:26:08+00:00

    a.(5x-4)^2-49x^2=(5x-4)^2-(7x)^2=(5x-4-7x).(5x-4+7x)=(-2x+4).(12x-4)

    b.9(2x+3)^2-4(x+1)^2=9(4x^2+12x+9)-4(x^2+2x+1)=36x^2 + 108x+81-8x-16x-4=36x^2+84x+77

    c.(3x+1)^2-4(x-2)^2=(9x^2+6x+1)-4(x^2-2x+1)=9x^2+6x+1-4x^2+8x-4=5x^2+14x-3

    d.16(4x+5)^2-25(2x+2)^2=256x^2+640x-400-100x^2-200x-100=156x^2-440x-500

    e.4x^2(x+y)+9y^2(y-x)=4x^3+4x^2y+9y^3-9xy^2

    f.4x^3+24x^2-12xy^2=4x(x^2+6x-9y^2)

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )